Management Accounting Practice in Nepalese Commercial Banks - Karki, Chitra Bahadur (Journal of Management, 2021)
The paper aims to analyze the management accounting practice in Nepalese commercial banks. Primary data have been collected by using interview method and structured questionnaire. The accounting and audit department staff in the sample banks were served with questionnaires. The descriptive survey research has been utilized in this research. The study employed the simple percentage and simple average to analyze the research questions. A sample of six numbers Nepalese commercial banks has been considered with convenience sampling technique. The study foundthat various management accounting tools are in practice in Nepalese commercial banks and maximum Nepalese commercial banks use more than one management accounting tools.In addition, management accounting is important to Nepalese commercial banks’ management for planning, evaluating, controlling and decision making and there are various problems in practicing management accounting tools in Nepalese commercial banks, such as lack of expertise, lack of information about tools, lack of top management’s committee, accounting provisions of NRB, tax law compliances, high cost and so on.